The Role of Organizational Learning and Knowledge Capability in Innovation Implementation: A Systematic Literature Review - Syifa Alifia Putri; Nurul Safitri (Politeknik Siber Cerdika Internasional, 2026)
Background: Innovation is a critical factor for organizations to sustain competitiveness in dynamic environments. In this context, knowledge and learning capability are increasingly recognized as strategic resources that support innovation implementation. Objective: This study aims to identify and synthesize the role of knowledge and learning capability in organizational innovation using a systematic literature review approach. Methods: Data were collected from the Scopus database, resulting in 30 empirical articles published between 2015 and 2025, and analyzed using thematic analysis. Results: The findings reveal four main themes. First, organizational learning has a positive relationship with innovation capability and innovation performance. Second, organizational learning acts as a mediating mechanism linking organizational factors to innovation outcomes. Third, knowledge management, absorptive capacity, and dynamic capability form an integrated mechanism that enables organizations to manage and transform knowledge into innovation. Fourth, innovation serves as a key link between organizational learning and organizational performance. Conclusion: This study contributes by integrating knowledge-based view and organizational learning perspectives, highlighting that the effect of learning on performance is indirect through innovation. Practically, organizations need to strengthen learning processes and knowledge management to enhance competitiveness. The novelty of this review lies in synthesizing fragmented empirical findings into a single integrative framework that positions organizational learning simultaneously as an antecedent, mediator, and dynamic capability. Future research should extend data sources beyond Scopus and empirically validate the proposed integrative model across diverse industry and regional contexts.